Stability Issues of Welded Pipe Containing Pulsatile Flows (Journal of Engineering, 2006)
This paper deals with the dynamics and stability behavior of a welded pipe containing flowingfluid having a small harmonic component superposed. The equation of motion was derived torepresent the motion of a welded pipe conveying a pulsatile flow using a tensioned Euler- Bernoullibeam theory. The finite element analysis was used to simulate the harmonic motion of a welded pipeconveying fluid. It was shown that welded pipes with clamped-clamped and clamped-pinned supportsare subject to a multitude of parametric instabilities in all their modes. Stability maps are presented forparametric instabilities of welded pipe with clamped-clamped and clamped-pinned ends. It is foundthat the extent of the instability regions increases with flow velocity for clamped-clamped andclamped-pinned welded pipes. The most important consideration from a practical point of view is toavoid the onset of parametric resonance.